GENETIC ALGORITHM-BASED CLUSTERING OF WIRELESS SENSOR NETWORK WITH NOVEL DATA ENCRYPTION - Kumar, Bachu jayendra; K, Rajya Lakshmi devi; M, VERGIN RAJA SAROBIN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Wireless sensor networks (WSNs) have been used widely in so many applications. It is the most efficient way to monitor the information. There are so many ways to deploy the sensors. Many problems are not identified and solved. The main challenge of WSN is energy efficiency and information security. WSN power consumption is reduced by genetic algorithm-based clustering algorithm. Information from cluster head to base station may have a lot of chances to get hacked. The most reliable way to manage energy consumption is clustering, and encryption will suit best for information security. In this paper, we explain clustering techniques and a new algorithm to encrypt the data in the network.